Relevance of RNA to the therapeutic efficacy of mesenchymal stromal/stem cells extracellular vesicles - T. T. Tan; S. K. Lim (RNA Biology)
Mesenchymal Stromal/Stem Cells (MSCs) are among the most frequently studied cell types in clinical trials, and their small extracellular vesicles (sEVs) are now being extensively investigated for therapeutic applications. The RNA cargo of MSC-sEVs, particularly miRNAs and mRNAs, is widely believed to be a key therapeutic component of these vesicles. In this review, we critically examine using first principles and peer-reviewed literature, whether MSC- extracellular vesicles (MSC-EVs) can deliver sufficient quantity of functional miRNA or mRNA to target compartments within recipient cells to elicit a pharmacological response. Several RNA sequencing studies reveal that miRNAs are underrepresented in the small RNA population of MSC-sEVs compared to the parent MSCs. Additionally, the majority of miRNAs are mature forms that are not associated with Argonaute (AGO) proteins, essential for their function in RNA-induced silencing complexes (RISCs). Compounding this, cellular uptake of EVs is generally inefficient, with less than 1% being internalized, and only a fraction of these reaching the cytosol. This suggests that EVs may not deliver miRNAs in sufficient quantities to meaningfully interact with AGO proteins, either through canonical or non-canonical pathways, or with other proteins like Toll-like receptors (TLRs). Further, MSC-sEV RNAs are generally small, with sizes less than 500 nucleotides indicating that any mRNA present is likely fragmented as the average mammalian mRNA is approximately 2000 nucleotides, a fact confirmed by RNA sequencing data. Together, these findings challenge the notion that RNA, particularly miRNAs and mRNAs, are primary therapeutic attributes of MSC-sEVs.